Circular Business Model Innovation: Integrating Design, Digitalization, and Institutional Perspectives for Sustainable Value Creation - Rajesh V. Menon (Academic Reseach Library for International Journal of Computer Science & Information System, 2025)
The transition toward circular economy paradigms has become a central focus in sustainability research and practice, emphasizing the need for innovative business models that extend product life cycles, minimize resource consumption, and maximize economic and environmental value. This study examines the multidimensional integration of circular business model innovation, product design strategies, and digital capabilities, with particular attention to institutional and organizational factors shaping adoption. Drawing on a comprehensive review of literature spanning circular economy frameworks, sustainable business model archetypes, digital business strategy, and resource management, this research identifies critical enablers, barriers, and mechanisms for implementing circular business models. Methodologically, this paper employs a qualitative synthesis approach, combining theoretical insights with empirical evidence from case studies and prior analyses. The findings reveal that successful circular business models require alignment between product design, organizational capabilities, stakeholder collaboration, and regulatory support, mediated by technological innovations such as big data analytics, smart systems, and digital platforms. Furthermore, institutional pressures, legitimacy strategies, and consumption policies significantly influence the uptake and diffusion of circular practices. The study highlights the necessity of viewing circular business models not only as economic instruments but as socio-technical and institutional innovations capable of fostering systemic sustainability transitions. By elucidating these linkages, this research offers both theoretical and practical guidance for corporations, policymakers, and academics aiming to advance circular economy principles. Implications for future research include the need for longitudinal studies to assess dynamic interactions among design, technology, and institutional factors, as well as the development of integrative evaluation frameworks for measuring circular performance.